Where there is no research: a bibliometric analysis of health research output from the resource-constrained Bihar state of India - Vikash R Keshri; Nutan S Tigga (Journal of Global Health Reports)
# Background Significant gap exists in health research output globally, both in terms of geographic distribution and priorities. In India, wide inter-state disparity in health research output is reported and eight large states with a combined population of nearly half of India contribute to less than one-tenth of total research output. Bihar is one of the most resource-constrained states in this group with multiple health systems challenges. The objectives of this study were to understand the trend, distribution, focus, actors, and funding sources of health research on Bihar in order to propose policy recommendations.